Travel Time Behavior Study of Malang-Denpasar Intercity Bus Considering Sailing Time of Ketapang-Gilimanuk - M.i Fatkhurrozi; D. K. Sudarsana; D. Yuniar; A. Suraji (JOURNAL OF SCIENCE AND APPLIED ENGINEERING, 2021)
The study intends to acquire travel time behavior needed by Malang-Denpasar intercity bus (AKAP) considering sailing time of Ketapang-Gilimanuk. This research is a new thing to find out the inter-city bus travel time between islands. Where in this study the bus route connects the island of Java with the island of Bali. The interesting thing is that the travel time during the crossing at the port is part of the overall travel time identification. In addition, the presentation method using a trajectory table for inter-city bus travel routes is a more interesting presentation. Travel time of the bus is achieved by moving observer method (actual survey) where the surveyor is on the bus to track the travel. Interview is also conducted to get the experience of the respondents. The results are displayed in trajectory curve to present travel speed in each segment. In this study there are limitations that were carried out due to limited resources. This survey was only conducted in one round trip and 2 surveyors were mobilized. And what was noted during the survey was more about the travel time aspect. The results of this study provide an overview of travel time in outbound and inbound. In addition, the delay time that occurs during the trip is also identified. Actual survey shows that outbound journey is longer (13.9 hours) than inbound (11.13 hours). Delay time of outbound is 3.16 hours while that of inbound is 1.28 hours. Interview results longer travel time than that of actual survey. While sailing time of Ketapang and Gilimanuk harbour satisfies the minimum standard.